Kulturowe uwarunkowania nazw alkoholowych napojów mieszanych sprzed roku 1989 i po nim w perspektywie kognitywno-stylistycznej - Sujkowska-Sobisz, Katarzyna (Postscriptum Polonistyczne, 2020)
Research on the names of mixed alcoholic drinks was inspired by the conviction that they were an important part of the code of culture. It is due to this code that a nation or a society can communicate or create its own identity. In the beginning of the article the position of alcoholic drinks in Polish customs from Middle Ages till contemporary times was shortly discussed. The author analyzed the names of the drinks that she classified as the ‘creative’ ones, with evident authorship. Four hundred names of drinks listed in a handbook written by Polish authors (Brodziński, Brodzińska 1993) and names of drinks that appear in the menu of 50 contemporary pubs, clubs and restaurants from different areas of Poland have been analyzed in the article. The attempt to create a typology of such names led to discovering structural metaphors that inspired particular names.